Pengaruh Kualitas Pelayanan Jasa Terhadap Kepuasan Pelanggan Pada Toko Emas Gajah, Batu - Alfiah Alfiah (STIE Kertanegara Malang, 2019)
Toko Emas Gajah is the best gold shop located in Batu City that provides the best after-sales and maintenance services for gold jewelry, and always provides the latest jewelry models.This study aims to explain the effect of service quality on customer satisfaction at TokoEmas Gajah. The measurement of the quality dimension uses five dimensions of service quality which consist of tangibles, reliability, responsiveness, assurance, and empathy dimensions. The research instrument used was a questionnaire distributed to 99 customers of Toko Emas Gajah which was taken using purposive sampling technique. Furthermore, the collected data was analyzed using multiple regression analysis to see the dimensions of service quality that were the most dominant influence on customer satisfaction at TokoEmas Gajah.The results of this study indicate the five variables of customer satisfaction simultaneously and partially have a significant effect on customer satisfaction at TokoEmas Gajah. While the factors that predominantly influence customer satisfaction in this gold shop are Reliability or reliability and are followed by variables of assurance, responsiveness and reliability.